Public Health Nurse Preceptors in Ireland: Exploring Recognition, Preparedness, and Support for Professional Development - Niamh Vickers; Denise Mc Guinness; Karl F. Conyard; Keighleigh Byrne; Deirdre McEldowney; Jacqueline Austin; Cathy Geraghty; Gonne C. Barry; Kate Frazer (Public Health Nursing, 2026)
ABSTRACT Background Preceptorship is a widely recognized pedagogy which positions experienced nurses as mentors, educators and assessors in the clinical environment. Public Health Nurse (PHN) preceptors are instrumental to the education and development of PHN students. This study aimed to evaluate PHN preceptors’ perceived recognition, preparedness and support in their roles and to determine overall satisfaction. Methods A cross‐sectional survey included a validated instrument modified for the Irish community context and convenience sampling methods to target PHN preceptors associated with one Higher Education Institution, following low‐risk ethical approval in 2024. Subscale domains included preparedness, recognition, support and satisfaction. Data were analyzed using descriptive and inferential statistics and STROBE guidelines used for reporting. Results A response rate of 35.8% ( n = 86) was attained. The Preparedness domain demonstrated the highest consensus ( M = 12.48, SD = 2.06), indicating that respondents felt prepared for their Preceptorship role. Respondents demonstrated high levels of agreement with pedagogical competencies related to making objective student assessments and supporting skills development. Barriers included insufficient time to engage with preceptorship. The results reveal a disconnect between preceptors perceiving that they were highly valued by students but that the preceptorship role was not formally acknowledged as part of their workload at an organizational level. High attendance was reported at preceptor education sessions (87.2%) and a preference for future education to be delivered online (46.4%). Conclusion PHN preceptors are critical to integrating theoretical learning in the clinical practice environment. While results demonstrate high satisfaction and confidence, significant challenges exist at the systems level to balance the role and demands of preceptorship, within workloads due to time constraints. At a time when primary care settings are being prioritized for healthcare, the workforce challenges need to be understood and solutions co‐created. Future research should incorporate qualitative methods to explore the experiences of preceptors and PHN students.